Acute urinary retention in women due to urethral calculi: A rare case - Turo, Rafal (Canadian Medical Association, 2014)
We present a case of a 51-year-old woman with acute urinary retention caused by a urethral calculus. Urethral calculi in women are extremely rare and are usually formed in association with underlying genitourinary pathology. In this case, however, no pathology was detected via thorough urological evaluation. We discuss the pathogenesis, clinical presentation and treatment of urethral calculi. To our knowledge, this is the second reported case of a primary urethral calculus in a female with an anatomically normal urinary tract and the first in a middle-aged Caucasian female.